Open Science in Open Innovation Model in Covid-19 Times: Evidence on Scientific Collaboration - Elzbieta POHULAK-ZOLEDOWSKA (Communications of International Proceedings, 2021)
The hereby article concerns the issue of open innovation model adoption to pandemic circumstances. Open innovation model first introduced in pharmaceutical companies was to make innovation process more dynamic, cheaper and prompt. The open innovation paradigm in pre-pandemic times consisted of actors with a different scope of authorization to process and use the knowledge. The major artifact of opening the innovation process was the free knowledge flow. During pandemic there was an increase in expectations of the pharmaceutical industry. The health crisis made the pharmaceutical industry the “industry of hope” and this extraordinary circumstances made the open innovation even more open, more institutionalized and collaborative. The goal of the article is to show the change of open innovation process in the pandemic times.
Keywords: Open Innovation; Knowledge Economy; Open Science.